2014
DOI: 10.3389/fnagi.2014.00113
|View full text |Cite
|
Sign up to set email alerts
|

A rightward shift in the visuospatial attention vector with healthy aging

Abstract: The study of lateralized visuospatial attention bias in non-clinical samples has revealed a systematic group-level leftward bias (pseudoneglect), possibly as a consequence of right hemisphere (RH) dominance for visuospatial attention. Pseudoneglect appears to be modulated by age, with a reduced or even reversed bias typically present in elderly participants. It has been suggested that this shift in bias may arise due to disproportionate aging of the RH and/or an increase in complementary functional recruitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
66
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 125 publications
(235 reference statements)
5
66
3
Order By: Relevance
“…The present results for visual bisection are at odds with some published data which has suggested that older adults show reduced pseudoneglect (Fujii et al, 1995;Stam & Bakker, 1990;Benwell et al, 2014b;Schmitz & Peigneux, 2011;Barrett & Craver-Lemley, 2008;Goedert et al, 2010), so it is necessary to consider why this may be. One speculative candidate may be method: Benwell et al (2014b) and Schmitz & Peigneux (2011) both used variants of the 'Landmark' task, in which judgements are made about a pre-bisected presented line: it may be that this task requires more fine grained perceptual evaluation, and thus elicits higher levels of real or perceived difficulty, , and that this causes additional recruitment of areas in the contralateral hemisphere, which is a clear possibility under the CRUNCH model of aging (Reuter-Lorenz and Cappell, 2008) and may also be so under the HAROLD model (Cabeza, 2002;Cabeza, et al, 1997;2002).…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…The present results for visual bisection are at odds with some published data which has suggested that older adults show reduced pseudoneglect (Fujii et al, 1995;Stam & Bakker, 1990;Benwell et al, 2014b;Schmitz & Peigneux, 2011;Barrett & Craver-Lemley, 2008;Goedert et al, 2010), so it is necessary to consider why this may be. One speculative candidate may be method: Benwell et al (2014b) and Schmitz & Peigneux (2011) both used variants of the 'Landmark' task, in which judgements are made about a pre-bisected presented line: it may be that this task requires more fine grained perceptual evaluation, and thus elicits higher levels of real or perceived difficulty, , and that this causes additional recruitment of areas in the contralateral hemisphere, which is a clear possibility under the CRUNCH model of aging (Reuter-Lorenz and Cappell, 2008) and may also be so under the HAROLD model (Cabeza, 2002;Cabeza, et al, 1997;2002).…”
contrasting
confidence: 99%
“…The observation of consistent lateral bias in representational tasks like mental number line and tactile bisection are especially problematic under the HAROLD model with its focus on decreasing hemispheric asymmetry over age especially in prefrontal cortex, given the role Running Head: ADULT DEVELOPMENTAL TRAJECTORIES 26 prefrontal cortex is known to play in spatial memory (Courtney et al, 1998). For similar reasons, our findings are not in line with the right hemi-ageing model (Dolcos et al, 2002;Prodan et al, 2007) nor with findings indicating rightward biases for older adults (Benwell et al, 2014b).…”
contrasting
confidence: 72%
See 2 more Smart Citations
“…Results have shown that line length and fatigue have additive effects, suggesting that the bisection asymmetries for short and long lines are governed by a common set of processes. A similar additive effect was observed by Benwell, Thut, Grant, and Harvey (2014) for the effect of ageing, which is also known to reduce right hemisphere activity.…”
supporting
confidence: 74%